(untitled) (Iranian Journal of Kidney Diseases, 2024)
Introduction. Peritoneal dialysis (PD) is an effective treatment modality for advanced kidney failure, offering patients a significant degree of independence. However, the long-term use of PD is limited due to the degeneration of the peritoneal membrane, resulting in reduced dialysis adequacy. Evaluating the peritoneal membrane condition in patients with advanced kidney failure who are undergoing PD is challenging with existing methods. Therefore, this study aimed to investigate the correlation between 8-hydroxy-2’-deoxyguanosine (8OHDG) levels in the peritoneal solution of patients undergoing PD and various factors, such as peritoneal equilibration test (PET), dialysis adequacy (Kt/V), underlying diseases, serum ferritin, and albumin levels. 8OHDG is a sensitive marker of oxidative stress caused by DNA damage. Methods. A total of 56 patients were included in this cross-sectional study. Five milliliters of PD fluid were collected from the patients, and 8-OHdG levels were measured using ELISA method. Then, they were compared with PET, Kt/V, albumin, and ferritin markers in the patients’ files, and the results were analyzed by statistical tests. Results. The study examined the correlation between 8OHDG and other markers. It was found that this index had significant associations with PET and underlying HTN (P < .05), whereas no significant associations were identified with the other markers. Conclusion. The results of the present study demonstrate that the level of 8OHDG, as one of the oxidative stress markers, could be used to evaluate the function of the peritoneum in patients undergoing PD. DOI: 10.52547/ijkd.7654